Kewarganegaraan Ekologis dalam Pembangunan Kota Sehat Surakarta: (Kajian Literatur Tentang Kolaborasi Pemerintah dan Masyarakat dalam Pengelolaan Lingkungan Berkelanjutan) - Yohanes Octora Sinurat; Hasanudin Hasanudin; Siti Karlina; Wirda Rohma (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
This study explores how the concept of ecological citizenship can strengthen collaboration between the government and society in building a healthy city in Surakarta. Using a literature review method, it examines various studies related to ecological citizenship, community participation, and sustainable urban policy. The findings show that a healthy city is not only determined by government policy and infrastructure but also by citizens’ awareness and active involvement in environmental protection. The core values of ecological citizenship such as responsibility, participation, and environmental justice help cultivate collective behavior that supports urban ecological sustainability. The government plays a vital role as a facilitator of collaboration, while citizens act as key agents of innovation through community-based activities such as waste banks, urban gardens, and neighborhood greening. However, challenges remain, including limited resources, unequal participation, and low environmental awareness among some residents. Therefore, stronger synergy between public policy, environmental education, and civic engagement is needed to foster an ecological culture. This study concludes that a sustainable healthy city can only be achieved when ecological citizenship becomes part of the collective consciousness of all urban residents.